Duodenum-preserving pancreatic head resection compared to pancreaticoduodenectomy: A systematic review and network meta-analysis of surgical outcomes - Guo, Shixiang; Zhou, Qiang; Yang, Jiali; Tao, Junyu; Zhang, Junfeng; Wang, Huaizhi (Frontiers in Surgery, 2023)
Objectives In this systemic review and network meta-analysis, we investigated pancreaticoduodenectomy (PD), pylorus-preserving pancreaticoduodenectomy (PPPD), and different modifications of duodenum-preserving pancreatic head resection (DPPHR) to evaluate the efficacy of different surgical procedures. Methods A systemic search of six databases was conducted to identify studies comparing PD, PPPD, and DPPHR for treating pancreatic head benign and low-grade malignant lesions. Meta-analyses and network meta-analyses were performed to compare different surgical procedures. Results A total of 44 studies were enrolled in the final synthesis. Three categories of a total of 29 indexes were investigated. The DPPHR group had better working ability, physical status, less loss of body weight, and less postoperative discomfort than the Whipple group, while both groups had no differences in quality of life (QoL), pain scale scores, and other 11 indexes. Network meta-analysis of a single procedure found that DPPHR had a larger probability of best performance in seven of eight analyzed indexes than PD or PPPD. Conclusion DPPHR and PD/PPPD have equal effects on improving QoL and pain relief, while PD/PPPD has more severe symptoms and more complications after surgery. PD, PPPD, and DPPHR procedures exhibit different strengths in treating pancreatic head benign and low-grade malignant lesions. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022342427.